Medical students positions regarding resource allocation in times of crisis. (December 2022) - Minkin Levy, Daniel; Sagy, Iftach; Johansson Lipinski Lubianiker, Margaret; Jotkowitz, Alan
Objective: To compare the perspectives of medical students in the preclinical and clinical phases of medical training on the issue of rationing scarce medical resources in times of crisis. Methods: Questionnaire-based cross-sectional study. Results: A total of 201 participants took part in the study, with 100 participants in the preclinical phase group, and 101 in the clinical phase group. A multivariable analysis found that just 14.9% (n = 34) of the clinical phase students were willing to give a short-supplied blood unit to the first-arrived patient to the emergency department when more patients are expected compared to 63.9% in the preclinical group (n = 62) ( p  < 0.001, OR = 0.75 95% CI: 0.029−0.192). Seventy-four percent (n = 74) of the clinical phase students were found to be willing to remove a patient from a respirator to allocate it to an ill child compared to 35.7% (n = 35) in the preclinical phase group ( p  < 0.001, OR = 4.168 95% CI: 1.931−8.998). Of the clinical phase group, 46.6% (n = 41) were willing to allocate a short supplied flu medicine to a patient with poor prognosis compared to 57.7% (n = 56) in the preclinical phase group ( p  = 0.04, OR = 0.457 95% CI: 0.216−0.966). Conclusion: Clinical exposure during training may affect the way medical students make ethical decisions, independent of age, sex, as well as marital and parental status.